2022
DOI: 10.1039/d2qm00233g
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional BA2PbBr4-based wafer for X-rays imaging application

Abstract: As one of the most promising candidates for X-ray imaging materials, perovskite has received extensive attention. However, the poor stability and undesirable ion migration are still the hindrance on its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The superb penetration ability of X-ray makes X-ray imaging widely used and developed in fields such as medical diagnosis, industrial non-destructive detection, safety inspection, and nuclear safety detection. As an energy conversion layer in X-ray imaging systems, scintillators can effectively convert high-energy rays into visible light. Common commercial scintillators are some inorganic solid single crystals, such as NaI: TI, CsI: TI, Bi 4 Ge 3 O 12 (BGO), CdWO 4 (CWO), etc. However, there are problems such as high process costs, difficulties in large-size preparation, and poor moisture resistance. Therefore, in recent years, a new generation of scintillatorsmetal halide materialsgradually has the potential to replace traditional scintillators, receiving more and more research and attention. Among them, copper-based metal halide is one of the most widely studied lead-free metal halide scintillators due to its unique self-trapped exciton (STE) emission and performance advantages such as high photoluminescence quantum yield (PLQY), small self-absorption, and high X-ray absorption. …”
Section: Introductionmentioning
confidence: 99%
“…The superb penetration ability of X-ray makes X-ray imaging widely used and developed in fields such as medical diagnosis, industrial non-destructive detection, safety inspection, and nuclear safety detection. As an energy conversion layer in X-ray imaging systems, scintillators can effectively convert high-energy rays into visible light. Common commercial scintillators are some inorganic solid single crystals, such as NaI: TI, CsI: TI, Bi 4 Ge 3 O 12 (BGO), CdWO 4 (CWO), etc. However, there are problems such as high process costs, difficulties in large-size preparation, and poor moisture resistance. Therefore, in recent years, a new generation of scintillatorsmetal halide materialsgradually has the potential to replace traditional scintillators, receiving more and more research and attention. Among them, copper-based metal halide is one of the most widely studied lead-free metal halide scintillators due to its unique self-trapped exciton (STE) emission and performance advantages such as high photoluminescence quantum yield (PLQY), small self-absorption, and high X-ray absorption. …”
Section: Introductionmentioning
confidence: 99%
“…Owing to the same situation, similar results were observed for the BA 2 PbI 4 and BA 2 PbI 4 /BA 2 MAPb 2 I 7 perovskites, as shown in Figure 2 reported that high intensity XRD peaks of BA2MAPb2I7 crystals were obtained at the angles of 5.09°, 9.62°, 14.12°, 18.65°, 23.23°, 27.80° and 32.44° [33]. In addition, due to the continuity of the inorganic-organic-inorganic layer in the crystal structure of 2D OHP single crystals, the angle values at which XRD peaks increase regularly according to the d gap distance between the crystal planes [34][35][36]. Accordingly, the distance between the crystal planes of the synthesized 2D OHP single crystals was measured to be d=1.964nm and, using the Bragg equation (n𝜆 = 2𝑑𝑠𝑖𝑛𝜃), it was calculated that the difference between the angle values between each peak should be approximately 2𝜃=4.5°, which is consistent with the obtained results.…”
Section: Resultsmentioning
confidence: 95%
“…The average lifetime of BM 2 PbBr 4 was only 0.97 ns, which is much shorter than all previous reported perovskite single crystals and nanocrystals, such as CsPbBr 3 nanocrystals (44.6 ns), CsPbBr 3 nanosheets (8 ns), and BA 2 PbBr 4 single crystal (6.82 ns). [19,20,35] Moreover, we also measured the low temperature time dependent photoluminescence spectra to exclude the influence of non-radiative recombination (Figure 3f). The decay curves at 80 K follow single exponential decay behavior.…”
Section: Resultsmentioning
confidence: 99%